1997
DOI: 10.1002/(sici)1098-1136(199709)21:1<2::aid-glia2>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter proteins in brain: Delivery of glucose to neurons and glia

Abstract: Glucose is the principle energy source for the mammalian brain. Delivery of glucose from the blood to the brain requires transport across the endothelial cells of the blood‐brain barrier and into the neurons and glia. The facilitative glucose transporter proteins mediate these processes. The primary isoforms in brain are GLUT1, detected at high concentrations as a highly glycosylated form, (55 kDa) in blood‐brain barrier, and also as a less glycosylated, 45 kDa form, present in parenchyma, predominantly glia; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
364
0
17

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 580 publications
(410 citation statements)
references
References 123 publications
19
364
0
17
Order By: Relevance
“…This assumption is supported by isolated cell studies that have shown high glucose transport activity on neurons and glia (Lund-Andersen 1979;Vannucci et al, 1997). The in vivo magnetic resonance spectroscopy study of Gruetter et al (1996) found a significantly slower time course in the increase of brain glucose relative to plasma glucose during a rapid glucose infusion, which agreed with the kinetics predicted for uniform glucose distribution between brain compartments.…”
Section: Glucose Transport In Human Brain 489supporting
confidence: 53%
“…This assumption is supported by isolated cell studies that have shown high glucose transport activity on neurons and glia (Lund-Andersen 1979;Vannucci et al, 1997). The in vivo magnetic resonance spectroscopy study of Gruetter et al (1996) found a significantly slower time course in the increase of brain glucose relative to plasma glucose during a rapid glucose infusion, which agreed with the kinetics predicted for uniform glucose distribution between brain compartments.…”
Section: Glucose Transport In Human Brain 489supporting
confidence: 53%
“…The mRNA for insulin-responsive GLUT4 was expressed in about half of all neurons, but there were no significant intergroup differences in expression (Table 3). The possibility that neuronal glucosensing might be regulated by insulin's acting on GLUT4, as it is in peripheral tissues (34,35,52), was raised by the coexpression of GLUT4 and INS-R mRNA in 40 -75% of all neurons, regardless of their glucosensing properties (Table 3). Because there were no significant intergroup differences in coexpression, it is less likely that insulin-mediated glucose uptake might serve as an alternate mechanism of glucosensing.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose transport from blood into the brain is mediated by a facilitated diffusion-type transport system, that is members of the GLUT supergene family of integral membrane proteins (Maher et al, 1994;Vannucci et al, 1997;Shepherd and Kahn, 1999). Tissue-specific expression of one or more members determines the rate of glucose entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…As brain glucose metabolism could be adversely affected in some neurodegenerative disorders, including stressrelated neuropsychopathologies (reviewed in Peppard et al (1990), Hoyer (2000), Weinstock and Shoham (2004), Peters et al (2004)), we hypothesized that one mechanism of PPARg agonists' protection during stress exposure could be related to an increase in the cerebral metabolism of glucose. The delivery of glucose within the brain is mediated primarily by GLUT-1, present in the blood-brain barrier and in astrocytes and by GLUT-3 present in neurons (Vannucci et al, 1997;Pellerin, 2005). As 85% of the energy expenditure of the brain occurs in neurons (Attwell and Laughlin, 2001), and glucose is almost the only fuel used by the organ, we tested the possibility that the preventive effects of PPARg agonists are through glucose transporters, possibly through the neuronal component, GLUT-3.…”
Section: Introductionmentioning
confidence: 99%